2015
DOI: 10.1152/ajpheart.00528.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical model of platelet turnover in thrombocytopenic and nonthrombocytopenic preterm neonates

Abstract: Kulshrestha M, Sola-Visner M, Widness JA, Veng-Pedersen P, Mager DE. Mathematical model of platelet turnover in thrombocytopenic and nonthrombocytopenic preterm neonates. Am J Physiol Heart Circ Physiol 308: H68 -H73, 2015. First published October 31, 2014 doi:10.1152/ajpheart.00528.2013.-Neonatal thrombocytopenia affects 22-35% of all neonates admitted to neonatal intensive care units. The purpose of this study was to develop a mathematical model for characterizing platelet (PLT) kinetics in thrombocytopenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…In VLBW infants with severe thrombocytopenia associated with NEC or sepsis, IPF# is decreased by~50% (IPF# 4.7 Â 10 9 /L) [38]. This suggests that a decreased megakaryopoietic activity contributes to the development of severe thrombocytopenia [40]. In summary, the percentage of IPF (IPF%) is higher compared to controls in the case of platelet consumption, and normal in the case of bone marrow failure.…”
Section: Immature Platelet Fractionmentioning
confidence: 96%
See 1 more Smart Citation
“…In VLBW infants with severe thrombocytopenia associated with NEC or sepsis, IPF# is decreased by~50% (IPF# 4.7 Â 10 9 /L) [38]. This suggests that a decreased megakaryopoietic activity contributes to the development of severe thrombocytopenia [40]. In summary, the percentage of IPF (IPF%) is higher compared to controls in the case of platelet consumption, and normal in the case of bone marrow failure.…”
Section: Immature Platelet Fractionmentioning
confidence: 96%
“…Chronic platelet consumption, inadequate thrombopoietin production due to liver dysfunction, or rare congenital disorders in platelet production should be considered. The analysis of platelet counts in a small case series of very low birth weight infants demonstrated that the platelet life span is shortened from 10 to 2.5 days in thrombocytopenic infants [40]. Chronic liver dysfunction, particularly after prolonged parental nutrition or surgery for NEC with cholestasis, aggravates thrombocytopenia.…”
Section: Rare Causesmentioning
confidence: 99%
“…In contrast, AIPC is considered to specifically reflect the daily platelet production [ 23 ]. The role of AIPC in thrombocytopenia is similar to that of the reticulocyte production index in evaluating anemia: correction for mature platelets is not required because the lifespan of an immature platelet is less than 24 h [ 24 , 25 ]. Therefore, a low AIPC in thrombocytopenia suggests decreased thrombopoiesis, such as in aplastic conditions, or an inadequate megakaryocytic response [ 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been shown that a lower number of mature platelets during the latter half of the 1st week of life was associated with PDA in preterm infants, while immature platelets were not independently associated with PDA ( 55 ). Importantly, a mathematical model of platelet turnover in preterm infants demonstrated significantly shorter population survival values for immature platelets and shorter platelet life spans in thrombocytopenic vs. non-thrombocytopenic neonates, indicating a preferential depletion of older, more mature platelets in thrombocytopenic infants ( 56 ).…”
Section: Platelet Function and Pda Closure In Preterm Infantsmentioning
confidence: 99%